The Preprimary Grade as a Complete Learning Ecosystem: A Case of Two Schools in Zambezi Region, Namibia - Кеннет Нзвала (Preschool Education: Global Trends, 2025)
Objective. This qualitative paper investigated ‘The Preprimary Grade as a Complete Learning Ecosystem’ in Zambezi region of Namibia. This is a loaded clause which is unpacked as the study unfolds. The crux of the matter is that if teachers work to view the preprimary grades they teach as complete learning ecosystems, their teaching will be effective as learners will benefit substantially from variables that build and constitute learning as an ecosystem.